Penerapan Metode Fifo (First in First Out) dalam Menjaga Efektivitas Warehouse pada PT. Mutiara Luwuk Bintang Lestari - Fitri Sylvianti Titong (Syntax Corporation Indonesia, 2024)
Mutiara Luwuk Bintang Lestari still manages inventory data manually in notebooks, which are prone to loss, damage, and miscalculations, resulting in inaccurate data. This study aims to examine the application of the FIFO (First In First Out) method in maintaining the effectiveness of inventory management in the warehouse of PT. Mutiara Luwuk Bintang Lestari. The research method used is qualitative with a descriptive approach. Data was obtained through direct observation and analysis of documents related to the inventory management system. The results of the study show that the application of the FIFO method has proven to be effective in improving the accuracy of inventory data, speeding up the process of managing goods, and reducing potential losses due to recording errors. The application of this method resulted in an increase in profits, as seen in the calculation of the cost of sales of Olympic Cabinets of Rp 191,600,000, Plastic Chairs of Rp 51,450,000, and Frontliner Seats of Rp 887,200,000. Thus, FIFO-based inventory systems provide significant benefits in improving the operational efficiency of a company's warehouse.